A review on the upper atmospheric sodium observations from India: Insights. Issue 11 (1st June 2019) - Sarkhel, S.; Mondal, S.; Sekar, R.; Chakrabarty, D.; Sridharan, S.
Abstract: This review article briefly brings out the historical development of atmospheric sodium (Na) measurements over India and the importance of coordinated measurements with multiple techniques to address physical processes in the Earth's upper atmosphere. These measurements were initiated in the early 1970s by observing Na airglow emission intensities with broad band airglow photometer from Mt. Abu, a low-latitude hill station in India. Considerable amount of night-to-night variations in nocturnal emission intensities of the Na airglow were observed. Later, investigations regarding the dependence with the magnetic activities from the equatorial and low latitudes were carried out and double-humped structures in the nocturnal variation of intensities were reported. With the advent of Na lidar at Gadanki around 2005, the measurements of atmospheric neutral Na atom concentration became possible and more frequent occurrences of sporadic Na layers over the magnetic low latitude station compared to other latitudes were detected indicating the role played by electrodynamics. Later, a possible relationship between E-region field aligned plasma irregularities and the concentration of neutral Na atoms was investigated using coordinated measurements of VHF radar and Na lidar. Further, simultaneous measurements with Na lidar and a narrow band airglow photometer with narrow field of view brought out the importance of coordinated observation wherein the characterization of gravity waves could be carried out and also revealed the importance of collisional quenching due to ambient molecules in the Na airglow emission processes. In addition, combining the ground based measurements of Na lidar and meteor wind radar along with satellite measurements made possible to hypothesize the over-turning Kelvin–Helmholtz billow in the Na layer manifests "C-type" or inverted lambda shape structures in the height-time-concentration map of neutral Na atoms. This review paper presents a synoptic view mostly based on the previously reported observations of Na airglow emission, Na lidar and coordinated Na airglow and Na lidar observations from the Indian sector and highlights the importance of simultaneous measurements of mesospheric Na and its emissions along with satellite-borne measurements to address interesting geophysical processes in the Earth's upper atmosphere.